PENGARUH PERAN GURU TERHADAP KARAKTER PEDULI LINGKUNGAN SISWA SMA N 1 BENAI - Nurhayati Nurhayati; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Developing a community of environmental concerns may be effective through environmental education in schools. As a place of school learning has a special role to play, schools can help students to understand the impact of human behavior on this earth. However, the increasingly uncontrollable environmental problems show that environmental education has not yet succeeded in shaping the human character who cares about the environment. Based on the description of the background then the formulation of the problem in this study is 1. How the role of teacher to the environmental caring character of high students SMA N 1 Benai. 2. How is the caring character of high studen SMA N 1 Benai. 3. How is the influence of the teachers role to the environmental caring character of high students SMA N 1 Benai. This study aims to determine the effect of teacher's role on the environmental caring character of students in SMA N 1 Benai. Subjects in this study are SMA N 1 Benai and all students of grade X and XI SMA N 1 Benai. SMA N 1 Benai amounted to 53 people, and X students amounted to 186 students and XI students amounted to 194 students. In determining the sample using purposive sampling (ie 10% of the 53 teachers and 380 students to 5 teachers and 36 people students. Data gathered through observation, interviews, questionnaires, and documentation. In analyzing the data using quantitative discrete techniques using statistical tests.The results showed that there is a significant influence between the role of teachers to the students' environmental cares can be proved from the results of data analysis. The process of planting the role of teachers to the character of environmental care is quite effective. Test data analysis by using simple linear regression yield "F" count equal to 0.76, F count bigger than F table with significance 5% is equal to 0,02. So that hypothesis testing is accepted. Based on the above analysis test can be concluded that the teacher role to the formation of students' caring character.Keywords: Influence of Teacher's Role, Character, Caring Environment